1990
DOI: 10.1523/jneurosci.10-02-00613.1990
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomographic measurements of pulvinar activity during an attention task

Abstract: Positron emission tomographic scans were recorded from human subjects following an object-identification task, one version of which required attentional selection and the other version of which did not. In one experimental session, the attention-demanding displays were presented in the left visual field and the nonattention displays were presented in the right visual field. In a second session, the sides of the displays were reversed. Analysis of the scans indicated that, averaged across the 2 sessions, the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
182
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(196 citation statements)
references
References 32 publications
12
182
2
Order By: Relevance
“…These data are in agreement with both patterns of selective impairment in pulvinarlesioned monkeys (37), and with patterns of pulvinar glucose uptake in healthy human observers when they are required to identify an object within a cluttered visual array (26). The severity of the patients' impairment depended on the relative contrasts of target and distracters; as distracter contrast increased relative to the target, sensitivity to target features declined (experiment 1).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These data are in agreement with both patterns of selective impairment in pulvinarlesioned monkeys (37), and with patterns of pulvinar glucose uptake in healthy human observers when they are required to identify an object within a cluttered visual array (26). The severity of the patients' impairment depended on the relative contrasts of target and distracters; as distracter contrast increased relative to the target, sensitivity to target features declined (experiment 1).…”
Section: Discussionsupporting
confidence: 80%
“…Heretofore, neuropsychological studies in patients with pulvinar damage have found no evidence that distracters interfere with performance (22)(23)(24), and one study reports reduced flanker interference from contralesional distracters (25). Pulvinar activation has nevertheless been reported using fMRI or positron emission tomography in healthy human observers during filtering tasks or other attentional paradigms (8,(26)(27)(28)(29)(30). The lack of distracter interference effects in human neuropsychological studies may reflect the use of behavioral tasks that measured the effects of response conflict, rather than perceptual selection of stimuli based on their behavioral salience.…”
mentioning
confidence: 99%
“…The model postulates that the pulvinar nucleus of the thalamus has a crucial controlling role in the coordination of neural processing in sensory and association cortices. Other eural responses to salient isual stimuli J. S. Morris and others evidence for the model includes (i) the pulvinar's extensive reciprocal connections with visual cortical areas and other brain regions (Ungerleider et al 1983) ; (ii) electrophysiological recordings in monkeys of pulvinar responses to visual salience (Petersen et al 1987 ;Robinson & Petersen 1992) ; (iii) human studies showing attentional deficits with pulvinar lesions (Rafal & Posner 1987) ; and (iv) PET experiments demonstrating pulvinar activation in a selective attention task (LaBerge & Buchsbaum 1990). The specific responses to visual salience recorded in the pulvinar nucleus in the present study are consistent with these previous findings, and provide general support for the model.…”
Section: Discussionmentioning
confidence: 99%
“…It was hypothesized that the cerebellum is required for complex attentive control (e.g., Barrett et al, 2001). In human studies using PET, the thalamus was activated by tasks requiring selective attention (LaBerge and Buchsbaum, 1990). It is believed to play a role in visual search (Barrett et al, 2001).…”
Section: Backward L2-to-l1 Switchingmentioning
confidence: 99%